PERILAKU HOMOSEKSUAL ELTON HERCULES JOHN DAN DAVID JAMES FURNISH SEBAGAI SUMBER IDE PENCIPTAAN KARYA KRIYA LOGAM - ludira yudha (Saraswati)
Homosexuality is a condition where human behavior is abnormal. In the past, it is regarded as taboo but today it comes back and becomes a common phenomenon among societies. Many people get braver in showing their identity as homosexual in public consciously. The phenomenon then triggers several countries to make a policy legalizing homosexual marriage. The world is heading to the era of Sodom and Gomorrah again. Elton John, the British famous musician who is also an aristocrat of United Kingdom, does a homosexual marriage with his lover, David Furnish. His social stratum is potential in giving an inspiration and suggestion to the other homosexuals. In this Terminal Project, the behavior of both of them becomes the source of idea which is transformed into an artwork. The visual idea of the artwork is influenced by the objects around the living environment. This theme then becomes interesting for it is rarely explored.Through exploration, design, and realization as the main processes in creating the artwork, homosexuality is packaged with wires as the main material and knitting as the main technique. The combination of the material and the technique is a craftsmanship implementation which is closely connected with Craft. The working process is emphasizing on the carefulness in knitting the wires which become the main material. This creation is also using semiotic approach as the postmodern aesthetic characteristic which is constructed by signs.The creation of this Terminal Project produces five works. Through the artworks, the writer is aimed to express a rejection toward homosexual behavior subtly and elegantly. The artworks are the writer’s concrete contribution in giving refreshment in the form of either an idea or a visual artwork of metal to the writer’s academic environment. Obviously, these artworks will be a stimulant for the writer himself and the readers in creating an artwork in the future.Keywords: Homosexual, Elton John, David Furnish, Craft, Wire